The Effectiveness of Law Number 27 of 2022 Concerning Personal Data Protection in Combating Cybercrime in Indonesia - Teguh Satria Putra Pratama Sihotang; Elvira Dewi Ginting (LEGAL BRIEF, 2026)
The development of information technology brings new challenges to personal data protection in the digital world. This study aims to evaluate the effectiveness of personal data protection policies in Indonesia in preventing and addressing cybercrime. Using a qualitative approach and normative-empirical research, this study combines a doctrinal analysis of the legal framework stipulated in Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) with secondary data analysis in the form of reports, scientific journals, and cybercrime statistics. The results show that although the PDP Law represents a step forward in digital privacy protection, its implementation still faces significant challenges, such as weak law enforcement, a lack of supporting facilities, and low public awareness. The functional analysis in this study highlights the need for institutional strengthening, increased digital literacy, and the development of an independent monitoring system to ensure the effectiveness of personal data protection in Indonesia. This research is expected to provide constructive recommendations for improving national policies on personal data protection and strengthening digital social control to prevent cybercrime